2017
DOI: 10.1038/sj.bdj.2017.878
|View full text |Cite
|
Sign up to set email alerts
|

Holistic care should be coming your way

Abstract: In this Opinion article, Nairn Wilson argues that interprofessional, holistic healthcare provision greatly enhances general health and wellbeing. For dentistry-oral healthcare provision to realise its potential in whole patient care, it must be integral to developments in holistic healthcare provision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 5 publications
0
12
0
1
Order By: Relevance
“…Limiting factors have included poor awareness and acceptability of the role among dentists [18,20]. Other issues cited are a need for training of dentists themselves, such that they are equipped to lead a multi-disciplinary, integrated team [21] and the perennial challenge of the terms of the existing National Health Service (NHS) general dental services (GDS) contract in England, which largely measures clinical productivity through 'units of dental activity' (UDAs) [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Limiting factors have included poor awareness and acceptability of the role among dentists [18,20]. Other issues cited are a need for training of dentists themselves, such that they are equipped to lead a multi-disciplinary, integrated team [21] and the perennial challenge of the terms of the existing National Health Service (NHS) general dental services (GDS) contract in England, which largely measures clinical productivity through 'units of dental activity' (UDAs) [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Sir, Rai asked whether there is any official parameter for low/medium/high risk category which could be used for caries risk assessment. 1 This topic has been discussed by Doméjean et al 2 in the recent themed issue of minimum intervention in the BDJ. Scientific reviews of the literature have found that the single best indicator of a patient developing caries in the future is past caries experience.…”
Section: Caries Risk Assessment Toolsmentioning
confidence: 99%
“…3 Different caries risk assessment models have been developed to help dental professionals assess patients' caries risk. 2 While many dentists apparently do some type of informal caries risk assessment, there remains the need for broadly adopted ideally electronic caries risk assessment tools that can help dental professionals in establishing and documenting the caries risk status of their patients as well as tracking changes over time. Letters to the editor COMMENT Send your letters to the Editor, British Dental Journal, 64 Wimpole Street, London, W1G 8YS.…”
Section: Caries Risk Assessment Toolsmentioning
confidence: 99%
“…5 It may be because of a possible perception of dentistry as a 'poor relative' in relation to general medicine. 6 Nevertheless, there is scope for considering the place of dentistry in the new emerging organisational architecture of the NHS and its place in the wider health and social care context.…”
Section: Key Pointsmentioning
confidence: 99%